Implementation science in palliative care : recommendations for an education programme for hospice patients : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology (Endorsement in Health Psychology) at Massey University, Manawatu, New Zealand - Shaw, Rachel Amanda (Massey University, 2023)
There are a variety of approaches that can be used to develop education programmes targeted towards palliative care patients, and many intervention approaches have been trialled both locally and internationally. However, as with many forms of research, there is a gap between evidence-based findings being published and these findings making it into professional practice approaches. Implementation Science is one approach that attempts to bridge the gap between research and practice. This research aimed to discover what both patients and staff members at a Hospice facility felt were effective approaches to use when creating a patient-centred palliative care programme. In-depth interviews with semi-structured, open-ended questions were conducted with participants, who were asked to share their views on palliative care education, what makes a suitable patient programme, how to meet the cultural needs of patients attending the programme, and how to effectively engage patients in the programme. The interviews were recorded, transcribed, and then analysed using thematic analysis. The interviews were then compared with evidence-based research to attempt to bridge the gap between research and practical applications. Themes such as addressing stigma, relationship dynamics, practical group considerations, and the complexities of carer inclusion emerged from the interview findings. Recommendations were then made about specific ways an education programme can be developed for palliative care patients, using an Implementation Science model to guide these recommendations in a practical way.
Keywords: 520304 Health psychology